Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

A tale of two communication tools: discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2018)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.
Keywords: Applications programs; China; Collaborative learning; Collaborative virtual environments; Communication; Computer Mediated Communication; Computer Software; Computer assisted instruction--CAI; Content Analysis; Content analysis; Cooperative Learning; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational technology; Foreign Countries; Handheld Devices; Higher Education; Learning; Network Analysis; Network analysis; Preferences; Preservice Teachers; Social Networks; Social factors; Student Attitudes; Student Surveys; Synchronous Communication; Telecommunications; Tools; Undergraduate Students; __:import:01; __:match:final; __:matched; __:study_id:2096807; __finaldtb

A tale of two communication tools: discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2018)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.
Keywords: Applications programs; China; Collaborative learning; Collaborative virtual environments; Communication; Computer Mediated Communication; Computer Software; Computer assisted instruction--CAI; Content Analysis; Content analysis; Cooperative Learning; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational technology; Foreign Countries; Handheld Devices; Higher Education; Learning; Network Analysis; Network analysis; Preferences; Preservice Teachers; Social Networks; Social factors; Student Attitudes; Student Surveys; Synchronous Communication; Telecommunications; Tools; Undergraduate Students; __:import:01; __:match:final; __:matched; __:study_id:2096807; __finaldtb

Improving educational outcomes & reducing absenteeism at remote villages with mobile technology and WhatsApp: findings from rural India - Nedungadi, Prema; Mulki, Karunya; Raman, Raghu (Education and Information Technologies, 2018)
Reduction of teacher and student absenteeism, together with consistent teacher support and training, are critical factors in improving the quality of education in rural India. As part of an ongoing project involving schools and educational centers in rural areas spread across 21 Indian states, this study investigated how implementation of two simple, accessible technologies could not only reduce absenteeism but also increase teachers' effectiveness and improve student performance. In addition to students and teachers, key stakeholders included educational coordinators who provided support and monitoring regarding use of WhatsApp and two additional apps designed specifically to support simple educational improvements. In our study we coded and analyzed nine months of messages (n = 8968), both photographs and texts, posted by 26 participants. The number of text messages related to attendance was strongly positively correlated with frequency of interactions between coordinators and teachers. Our approach resulted in increased teacher and student attendance, as well as improvements in lessons and other planned educational activities. This model functions well in rural settings where there is poor internet connectivity and lack of supporting infrastructure. Remote schools can easily adopt this tablet-based model to reduce teacher absenteeism, improve teaching techniques, improve educational resources, and increase student performance.
Keywords: Absenteeism; Academic Achievement; Attendance; Attendance Patterns; Computer Oriented Programs; Computers--Information Science And Information Theory; ERIC, Current Index to Journals in Education (CIJE); Educational Opportunities; Educational Quality; Educational technology; Foreign Countries; ICT; India; Monitoring; Quality of education; Rural Areas; Rural areas; Rural education; School education; Software; Students; Teacher Effectiveness; Teacher absence; Teacher monitoring; Teachers; Tele-education; WhatsApp; __:import:01; __:match:final; __:matched; __:study_id:2097863; __finaldtb

Improving educational outcomes & reducing absenteeism at remote villages with mobile technology and WhatsApp: findings from rural India - Nedungadi, Prema; Mulki, Karunya; Raman, Raghu (Education and Information Technologies, 2018)
Reduction of teacher and student absenteeism, together with consistent teacher support and training, are critical factors in improving the quality of education in rural India. As part of an ongoing project involving schools and educational centers in rural areas spread across 21 Indian states, this study investigated how implementation of two simple, accessible technologies could not only reduce absenteeism but also increase teachers' effectiveness and improve student performance. In addition to students and teachers, key stakeholders included educational coordinators who provided support and monitoring regarding use of WhatsApp and two additional apps designed specifically to support simple educational improvements. In our study we coded and analyzed nine months of messages (n = 8968), both photographs and texts, posted by 26 participants. The number of text messages related to attendance was strongly positively correlated with frequency of interactions between coordinators and teachers. Our approach resulted in increased teacher and student attendance, as well as improvements in lessons and other planned educational activities. This model functions well in rural settings where there is poor internet connectivity and lack of supporting infrastructure. Remote schools can easily adopt this tablet-based model to reduce teacher absenteeism, improve teaching techniques, improve educational resources, and increase student performance.
Keywords: Absenteeism; Academic Achievement; Attendance; Attendance Patterns; Computer Oriented Programs; Computers--Information Science And Information Theory; ERIC, Current Index to Journals in Education (CIJE); Educational Opportunities; Educational Quality; Educational technology; Foreign Countries; ICT; India; Monitoring; Quality of education; Rural Areas; Rural areas; Rural education; School education; Software; Students; Teacher Effectiveness; Teacher absence; Teacher monitoring; Teachers; Tele-education; WhatsApp; __:import:01; __:match:final; __:matched; __:study_id:2097863; __finaldtb

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction--CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics--Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence